Rosmarinic acid nano delivery system as well as preparation method and application thereof
By using fish skin protein and chitosan to prepare the rosemary acid nanodelivery system, the problem of poor stability of rosemary acid is solved, and its antioxidant activity protection and radical scavenging ability are improved, which is suitable for the steady-stateization of food functional factors and nutrients.
Patent Information
- Application Number
- CN202411892332.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-21
AI Technical Summary
Rosemary acid has poor stability and low permeability, which limits its bioavailability and application range.
Rosemary acid nanodelivery system is prepared by freeze-drying method to improve its stability and protect its antioxidant activity.
It effectively improves the stability and antioxidant activity of rosemary acid, significantly enhances its ability to scavenge free radicals, and is suitable for the homeostasis of food functional factors or nutrients and the maintenance of antioxidant activity.
Smart Images

Figure CN119655442A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nutrient nano-embedding, and in particular relates to a rosmarinic acid nano-delivery system and a preparation method and application thereof. Background Art
[0002] Free radicals can participate in some beneficial aspects of the body's physiological activities, such as the synthesis of prostaglandins, prothrombin and collagen in the body, immunity, detoxification, cell proliferation and differentiation, and important physiological functions such as reproduction and embryonic development. However, too many free radicals can damage proteins, nucleic acids and cell membranes, leading to damage to normal cells and tissues in the human body, and ultimately forming a vicious cycle of excessive free radical production, reduced free radical scavenging ability and free radical accumulation in the body. It has been confirmed that free radical accumulation is involved in the occurrence and development of many diseases, such as inflammation, tumors, aging, blood diseases, etc. At present, the intervention of antioxidant nutrients and the improvement of lifestyle are the main methods to prevent and reduce the threat of free radicals to health.
[0003] Rosmarinic acid (RA) is a natural polyphenol compound extracted from plants such as rosemary, which has important biological activities such as antioxidant, anticancer, antibacterial, anti-inflammatory, antiviral and antiallergic. All these advantages have made it widely studied in the fields of food and biomedicine. Due to the two hydroxyl groups on the two aromatic rings of rosmarinic acid, it has a super strong ability to scavenge superoxide anions and hydroxyl radicals, and its antioxidant capacity is stronger than that of chlorogenic acid, vitamin E and caffeic acid. However, RA has some physical and chemical defects, such as poor stability and low permeability, which greatly reduce its bioavailability and limit its application. Therefore, there is an urgent need to develop a simple and effective delivery system to improve the stability of RA to protect its biological activity. Summary of the invention
[0004] The object of the present invention is to provide a rosmarinic acid nano delivery system and a preparation method and application thereof. The rosmarinic acid nano delivery system can effectively improve the stability of RA and protect its antioxidant activity.
[0005] The invention provides a rosmarinic acid nano delivery system, which comprises a wall material and inclusions; the wall material comprises fish skin protein and / or chitosan; and the inclusions comprise rosmarinic acid.
[0006] As a preferred embodiment, the mass ratio of the fish skin protein to chitosan is 0-5:0-5.
[0007] As a preferred embodiment, the fish skin protein includes black fish skin protein.
[0008] The present invention also provides a method for preparing the rosmarinic acid nano delivery system, comprising the following steps:
[0009] The rosmarinic acid aqueous solution is added dropwise into the wall material solution, and freeze-dried to obtain the rosmarinic acid nano delivery system.
[0010] As a preferred embodiment, the wall material solution includes a fish skin protein aqueous solution and / or a chitosan solution; the mass ratio of the fish skin protein to the chitosan is 0-5:0-5.
[0011] As a preferred embodiment, the concentration of the chitosan solution is 0.1wt%; the concentration of the fish skin protein aqueous solution is 0.1wt%; the concentration of the rosmarinic acid aqueous solution is 100μg·mL -1 .
[0012] As a preferred embodiment, the volume ratio of the rosmarinic acid aqueous solution to the wall material solution is 0.5-1.5:8-12.
[0013] As a preferred embodiment, the freeze-drying time is 36 to 48 hours.
[0014] As a preferred embodiment, after adding the rosmarinic acid aqueous solution dropwise into the wall material solution, the method further comprises adjusting the pH value of the rosmarinic acid nano delivery system to 6.8-7.2.
[0015] The present invention also provides application of the rosmarinic acid nano delivery system in preparing functional foods.
[0016] Beneficial effects: The present invention provides a rosmarinic acid nano-delivery system, which comprises a wall material and an inclusion; the wall material comprises fish skin protein and chitosan; the inclusion comprises rosmarinic acid. The rosmarinic acid nano-delivery system (RA@FSP / CS NCs) of the present invention not only maintains the excellent antioxidant activity of RA, but also has good stability. The system can effectively remove ABTS + Free radicals and hydroxyl (·OH) radicals are expected to be applied to the stabilization of food functional factors or nutrients and the maintenance of antioxidant activity.
[0017] The fish skin protein of the present invention can promote the growth of human umbilical vein endothelial cells (HUVEC) and has good biocompatibility, and can be used as a carrier for preparing food functional factors. At the same time, the fish skin protein has good ABTS + The present invention prepares RA@FSP / CS NCs from rosmarinic acid, fish skin protein and chitosan. Among various RA@FSP / CS NCs combinations, RA@FSP / CS 23 NCs showed the best antioxidant activity, ABTS + The free radical scavenging rate was 61.86%, followed by RA@FSP / CS 50NCs, ABTS + The free radical scavenging rate was 58.88%, RA@FSP / CS 32 ABTS of NCs + The free radical scavenging rate was the lowest, at 18.67%. Further studies showed that with the increase of RA@FSP / CS 23 As the amount of NCs added increases, ABTS + The free radical and hydroxyl radical (·OH) scavenging abilities of RA@FSP / CS 23 NCs have significant antioxidant activity, which is positively correlated with their concentration. 23 The high antioxidant capacity of NCs is mainly attributed to the o-diphenolic hydroxyl group and the conjugated double bond at the C-3 position in the RA structure. 23 NCs compared with RA and FSP / CS 23 The thermal stability of NCs is improved.
[0018] The present invention shows that adding rosmarinic acid (RA) to fish skin protein (FSP) and chitosan (CS) helps to form a denser nanostructure in the nanodelivery system. This denser nanostructure may be due to the presence of four phenolic hydroxyl groups and one carboxyl group in the RA molecule, which can interact with the NH groups in the protein molecules to form hydrogen bonds, thereby acting as a "bridge" between molecules. This interaction increases the cohesion of the nanodelivery system material and enhances the dominant role of non-covalent interactions between fish skin protein (FSP), chitosan (CS) and rosmarinic acid (RA). TEM results show that RA@FSP / CS 23 NCs have a distinct spherical structure, which is similar to that of FSP / CS 23 NCs are more regular than those of RA@FSP / CS, indicating that the introduction of RA significantly improves the 23 NCs microstructure. With the increase of CS ratio, the encapsulation efficiency of RA increased from 57.43% to 81.47%. When the ratio of fish skin protein to chitosan changed from 3:2 to 2:3, the encapsulation efficiency of RA increased from 60.68% to 71.42%, indicating that chitosan significantly improved the encapsulation efficiency of RA. This improvement may also be attributed to the interaction between RA, CS and FSP, which promoted the embedding of RA in FSP / CS wall materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings and appendices required for use in the embodiments.
[0020] Figure 1 The cell viability bar graph of fish skin protein at different concentrations in Example 1;
[0021] Figure 2 is the antioxidant activity of the fish skin protein of Example 2, wherein a is the ABTS treated with fish skin protein at different concentrations + UV spectra of b, ABTS of fish skin protein with different concentrations + Clearance bar graph;
[0022] Figure 3 The intuitive diagram of RA@FSP / CS NCs under different FSP:CS wall material mass ratios in Example 3, where a is a fresh suspension and b is a suspension after standing for 24 hours; 1, 2, 3, 4, 5, and 6 represent RA@FSP / CS NCs, respectively. 50 NCs, RA@FSP / CS 41 NCs, RA@FSP / CS 32 NCs, RA@FSP / CS 23 NCs, RA@FSP / CS 14 NCs and RA@FSP / CS 05 NCs;
[0023] Figure 4 FSP / CS of Example 3 23 NCs and RA@FSP / CS 23 Intuitive pictures and microstructures of NCs, where a is fresh suspension and b is suspension after 24 h of standing, where 1 is water and 2 is FSP / CS 23 NCs, 3 are RA@FSP / CS 23 NCs, c and d are FSP / CS 23 NCs and RA@FSP / CS 23 Scanning electron microscopy (SEM) images of NCs, e and f are FSP / CS 23 NCs and RA@FSP / CS 23 Transmission electron microscopy (TEM) images of NCs;
[0024] Figure 5 It is a bar graph of the encapsulation efficiency of RA in RA@FSP / CS NCs at different FSP:CS wall material mass ratios in Example 4;
[0025] Figure 6 The RA@FSP / CS NCs nano-delivery system material of Example 5 includes ABTS + The clearance rate of ABTS + Visual diagram of scavenging activity, b is ABTS +UV spectra of the removal rate, c is the ABTS of RA@FSP / CS NCs at different FSP:CS wall material mass ratios + The clearance rate;
[0026] Figure 7 RA@FSP / CS of Example 6 23 NCs nano-delivery system materials include ABTS + The clearance rate of RA@FSP / CS 23 NCs-treated ABTS + UV spectrum of ABTS + Bar graph of clearance rate;
[0027] Figure 8 RA@FSP / CS of Example 7 23 The scavenging rate of ·OH of NCs nanodelivery system materials, where a is RA@FSP / CS 23 Visual diagram of ·OH scavenging activity of NCs, b is different contents of RA@FSP / CS 23 UV spectra of ·OH treated with NCs, c is different contents of RA@FSP / CS 23 ·OH radical scavenging rate of NCs;
[0028] Fig. 9 RA, FSP / CS of Example 8 23 NCs, RA@FSP / CS 23 Thermogravimetric analysis of NCs. DETAILED DESCRIPTION
[0029] The present invention provides a rosmarinic acid nano delivery system, which includes a wall material and an inclusion; the wall material includes fish skin protein and chitosan; the inclusion includes rosmarinic acid. As a specific embodiment, adding rosmarinic acid (RA) to fish skin protein and chitosan helps to form a denser nano structure in the nano delivery system, and this denser nano structure may be due to the presence of four phenolic hydroxyl groups and one carboxyl group in the RA molecule, which can interact with the NH group in the protein molecule to form a hydrogen bond, thereby acting as a "bridge" between molecules, and this interaction increases the cohesion within the nano delivery system material and enhances the dominant role of the non-covalent interaction between fish skin protein (FSP), chitosan (CS) and rosmarinic acid (RA).
[0030] The mass ratio of fish skin protein and chitosan of the present invention is 0-5:0-5. In a specific embodiment, the mass ratio can be 5:0, 4:1, 3:2, 2:3, 1:4, 0:5, 5:1, 5:2, 5:3, 5:4, 4:2, 4:3, 4:5, 3:1, 3:4, 3:5, 2:1, 2:4, 2:5, 1:1, 1:2, 1:3, 1:4, 1:5, 0:1, 0:2, 0:3 or 0:4. As a specific embodiment, when the mass ratio of FSP and CS is 5:0, the rosmarinic acid nano delivery system is named RA@FSP / CS. 50 NCs, when the mass ratio of FSP to CS was 4:1, the rosmarinic acid nanodelivery system was named RA@FSP / CS 41 NCs, when the mass ratio of FSP to CS was 3:2, the rosmarinic acid nanodelivery system was named RA@FSP / CS 32 NCs, when the mass ratio of FSP to CS was 2:3, the rosmarinic acid nanodelivery system was named RA@FSP / CS 23 NCs, when the mass ratio of FSP to CS was 1:4, the rosmarinic acid nanodelivery system was named RA@FSP / CS 14 NCs, when the mass ratio of FSP to CS was 0:5, the rosmarinic acid nanodelivery system was named RA@FSP / CS 05 NCs. As a specific implementation, RA@FSP / CS 23 NCs showed the best antioxidant activity among all groups, ABTS + The free radical scavenging rate was 61.86%, followed by RA@FSP / CS 50 NCs, ABTS + The free radical scavenging rate was 58.88%, RA@FSP / CS 32 ABTS of NCs + The free radical scavenging rate was the lowest, at 18.67%.
[0031] The fish skin protein of the present invention includes black fish skin protein; the black fish skin protein of the present invention can promote the growth of human umbilical vein endothelial cells (HUVEC), has good biocompatibility, and can be used as a carrier for preparing food functional factors. At the same time, the black fish skin protein has good ABTS +As a specific embodiment, the method for preparing the black fish skin protein is as follows: soak the fish skin slices with a 0.01M NaOH solution containing 1% (w / v) H2O2 until the surface pigment is removed, wash the fish skin slices with water for 3 to 4 times, drain the water, soak the fish skin slices in a 10% (v / v) isopropanol solution, the weight ratio of the fish skin slices to the 10% isopropanol solution is 1:20, and stir magnetically for 16 hours; wash the fish skin slices with water to remove the residual isopropanol, add 100 mL of 0.05M acetic acid solution, magnetically stirred for 10 minutes, and after removing the acetic acid solution, the fish skin slices were washed with water for 3 times; the fish skin slices were placed in 10 times the weight of ultrapure water, and heated in a water bath at 45°C for 12 hours; the supernatant was collected by filtration and centrifugation (7000×g), and dialyzed to neutrality using a dialysis bag (8000-14000 kDa) and ultrapure water; the FSP was stored at -80°C overnight, and freeze-dried using a vacuum freeze dryer to obtain the black fish skin protein.
[0032] The present invention also provides a method for preparing the rosmarinic acid nano delivery system, comprising the following steps:
[0033] Add the rosmarinic acid aqueous solution dropwise to the wall material solution, freeze-dry for 36 to 48 hours to obtain the rosmarinic acid nano delivery system. In a specific embodiment, the freeze-drying time can be 36 hours, 37 hours, 38 hours, 39 hours, 40 hours, 41 hours, 42 hours, 43 hours, 44 hours, 45 hours, 46 hours, 47 hours or 48 hours. As a specific embodiment, the material obtained before freeze drying is a liquid rosmarinic acid nano delivery system material, and the material obtained after freeze drying is a solid rosmarinic acid nano delivery system material, and the solid rosmarinic acid nano delivery system material is a white powder. As a specific embodiment, with the RA@FSP / CS 23 As the amount of NCs added increases, ABTS + The free radical and hydroxyl radical (·OH) scavenging abilities of RA@FSP / CS 23 NCs have significant antioxidant activity, which is positively correlated with their concentration. 23 The high antioxidant capacity of NCs is mainly attributed to the o-diphenolic hydroxyl group and the conjugated double bond at the C-3 position in the RA structure.
[0034] The wall material solution of the present invention includes a fish skin protein aqueous solution and / or a chitosan solution; the mass ratio of the fish skin protein and chitosan is 0-5:0-5. In a specific embodiment, the mass ratio can be 5:0, 4:1, 3:2, 2:3, 1:4, 0:5, 5:1, 5:2, 5:3, 5:4, 4:2, 4:3, 4:5, 3:1, 3:4, 3:5, 2:1, 2:4, 2:5, 1:1, 1:2, 1:3, 1:4, 1:5, 0:1, 0:2, 0:3 or 0:4. As a specific embodiment, the preparation method of the wall material solution is to add the fish skin protein aqueous solution to the chitosan solution under magnetic stirring conditions to obtain a wall material solution. When the mass ratio of FSP and CS is 5:0, the wall material solution is named FSP / CS 50 NCs, when the mass ratio of FSP to CS is 4:1, the wall material solution is named FSP / CS 41 NCs, when the mass ratio of FSP to CS is 3:2, the wall material solution is named FSP / CS 32 NCs, when the mass ratio of FSP to CS is 2:3, the wall material solution is named FSP / CS 23 NCs, when the mass ratio of FSP to CS is 1:4, the wall material solution is named FSP / CS 14 NCs, when the mass ratio of FSP to CS is 0:5, the wall material solution is named FSP / CS 05 NCs.
[0035] The concentration of the chitosan solution of the present invention is 0.1wt%; the concentration of the rosmarinic acid aqueous solution is 100μg·mL -1 As a specific embodiment, the chitosan solution is prepared by dissolving 0.1 g of chitosan in 100 mL of 1% (v / v) acetic acid aqueous solution, and magnetically stirring to prevent chitosan from adhering to the wall to obtain a chitosan solution with a concentration of 0.1 wt %; the rosmarinic acid aqueous solution is prepared by dissolving rosmarinic acid in water to obtain a solution with a concentration of 100 μg·mL -1 of rosmarinic acid in water.
[0036] The concentration of the fish skin protein aqueous solution of the present invention is 0.1wt%. As a specific embodiment, the method for preparing the fish skin protein aqueous solution is to dissolve the fish skin protein in pure water and dissolve it in a 37°C water bath to obtain a fish skin protein aqueous solution with a concentration of 0.1wt%. As a specific embodiment, TEM results show that RA@FSP / CS 23 NCs have a more obvious spherical structure, which is different from FSP / CS 23 NCs are more regular than those of RA@FSP / CS, indicating that the introduction of RA significantly improves the 23NCs microstructure. As a specific embodiment, the encapsulation efficiency of RA increased from 57.43% to 81.47% with the increase of CS ratio. When the ratio of fish skin protein to chitosan changed from 3:2 to 2:3, the encapsulation efficiency of RA increased from 60.68% to 71.42%, indicating that chitosan significantly improved the encapsulation efficiency of RA. This improvement may also be attributed to the interaction between RA, CS and FSP, which promoted the embedding of RA in the FSP / CS composite wall material.
[0037] The volume ratio of the rosmarinic acid aqueous solution to the wall material solution of the present invention is 0.5-1.5:8-12. In a specific embodiment, the volume ratio can be 1:10, 0.5:8, 0.5:9, 0.5:10, 0.5:11, 0.5:12, 0.6:8, 0.6:9, 0.6:10, 0.6:11, 0.6:12, 0.7:8, 0.7:9, 0.7:10, 0.7:11, 0.7:12, 0.8:8, 0.8:9, 0.8:10, 0.8:11, 0.8:12, 0.9:8, 0.9:9, 0. 1.4:8, 1.4:9, 1.4:10, 1.4:11, 1.4:12, 1.5:8, 1.5:9, 1.5:10, 1.5:11, or 1.5:12.
[0038] After the rosmarinic acid aqueous solution is added dropwise to the wall material solution, the present invention further includes adjusting the pH value of the rosmarinic acid nano delivery system to 6.8-7.2. In a specific embodiment, the pH value can be adjusted to 6.8, 6.9, 7.0, 7.1 or 7.2. As a specific embodiment, RA@FSP / CS 23 NCs compared with RA and FSP / CS 23 The thermal stability of NCs is improved.
[0039] The present invention also provides the use of the rosmarinic acid nano delivery system or the rosmarinic acid nano delivery system prepared by the preparation method in the preparation of functional foods.
[0040] Unless otherwise specified, the present invention has no special requirements for the preparation raw materials, and commercially available products known to those skilled in the art can be used.
[0041] To further illustrate the present invention, a rosmarinic acid nano delivery system provided by the present invention, a preparation method thereof and an application thereof are described in detail below in conjunction with examples, but they should not be construed as limiting the scope of protection of the present invention.
[0042] The rosmarinic acid (RA) used in the following examples was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a catalog number of 20283-92-5; chitosan (CS) was purchased from Shanghai McLean Biochemical Technology Co., Ltd. with a catalog number of 9012-76-4; dialysis bags were purchased from Beijing Solebow Biotechnology Co., Ltd. with a catalog number of Y1073; hydrogen peroxide was purchased from Shandong Lierkang Medical Technology Co., Ltd.; sodium hydroxide was purchased from Tianjin Fengchuan Chemical Reagent Technology Co., Ltd. with a catalog number of Jin XK13-011-10003; isopropanol and acetic acid were purchased from Sinopharm Chemical Reagent Co., Ltd. with a catalog number of 80109228 for isopropanol; the catalog number of acetic acid is 10000208; ABTS was purchased from Shanghai McLean Biochemical Technology Co., Ltd. with a catalog number of 30931-67-0; persulfate Potassium was purchased from Tianjin Fengchuan Chemical Reagent Technology Co., Ltd. with the catalog number 7727-21-1, TMB was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with the catalog number 54827-17-7; ferrous sulfate was purchased from Sigma-Aldrich (Beijing) Biotechnology Co., Ltd. with the catalog number 7782-63-0, DMSO was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with the catalog number 67-68-5; HUVEC cells were purchased from Shanghai Sime Biotechnology Co., Ltd. with the catalog number STM-CE-1001; DEME medium was purchased from Thermo Fisher Suzhou Instrument Co., Ltd. with the catalog number C11995500BT; MTT was purchased from Sigma-Aldrich (Beijing) Biotechnology Co., Ltd. with the catalog number 298-93-1.
[0043] Example 1 Extraction of fish skin protein and cell activity of fish skin protein
[0044] (1) Extraction of fish skin protein
[0045] The scales of fresh black fish skin were removed, the skin was cut into small pieces, and rinsed with ultrapure water for 4 times. The water was squeezed out of the chopped and washed fish skin slices with gauze, and then weighed accurately. Under magnetic stirring, the fish skin slices were immersed in a 0.01M NaOH solution containing 1% (w / v) H2O2 to remove surface pigments. The immersion solution was changed every 8 hours until it was no longer turbid. Subsequently, the treated fish skin slices were washed with ultrapure water for 4 times, the water was drained thoroughly, and then the fish skin slices were immersed in a 10% (v / v) isopropanol solution with a weight ratio of 1:20 for the fish skin slices and magnetic stirring for 16 hours to remove fat from the skin. Next, the fish skin was washed several times with ultrapure water to remove residual isopropanol. 100mL of 0.05M acetic acid solution was added, followed by magnetic stirring for 10 minutes to ensure that the fish skin sample was fully expanded. The acetic acid solution was then removed by gauze filtration, and the swollen fish skin slices were washed three times with ultrapure water. The fish skin slices were placed in a beaker filled with 10 times the weight of ultrapure water and heated in a 45°C water bath for 12 hours under magnetic stirring. Subsequently, the supernatant was collected by filtration and centrifugation (7000×g), and dialyzed to neutrality using a dialysis bag (8000-14000kDa) and ultrapure water. Finally, the FSP was stored at -80°C overnight and freeze-dried using a vacuum freeze dryer to obtain fish skin protein.
[0046] (2) Cellular activity of fish skin protein (FSP)
[0047] Human umbilical vein endothelial cells (HUVEC) were seeded in 96-well plates at a seeding density of 1×10 4 cells. Then, the 96-well plate was placed in an incubator (37°C, 5% CO2) until it adhered to the wall, the DEME medium was discarded, and the prepared DEME medium was added (different concentrations of fish skin protein 5μg / mL, 25μg / mL, 50μg / mL, 100μg / mL, and 200μg / mL were added to the prepared DEME medium), and cultured in the incubator for 24h and 72h. After incubation, the prepared DEME medium was discarded. Then, 100μL of thiazolyl blue tetrazolium bromide (MTT) (1mg / mL) and fresh DEME medium were added to each well. The 96-well plate was cultured in an incubator (37°C, 5% CO2) for 4 hours, and then the medium and MTT were removed. 150μLDMSO was added to each well to dissolve the generated purple formazan crystals. Before measurement, the 96-well plate was placed in an incubator (37°C, 5% CO2) for 5 minutes. Finally, to assess cell viability, the absorbance at 490 nm was recorded using a microplate reader, and the cell viability was calculated.
[0048]
[0049] Here, A0 is the absorbance (490 nm) of the solution treated with ultrapure water, and A is the absorbance (490 nm) of the solution treated with different samples (experimental groups).
[0050] like Figure 1 As shown in Table 1, the cytotoxicity of fish skin protein (FSP) to HUVEC cells was studied by MTT method. It was found that the obtained FSP was non-toxic to HUVEC cells at different concentrations. In addition, the growth of HUVEC cells was promoted with the increase of FSP concentration, and when the FSP concentration was 200 μg / mL, the difference was significant compared with 0-100 μg / mL. The non-toxicity of FSP indicates that they have good biocompatibility, which lays a foundation for the preparation of food functional factor embedding carriers.
[0051] Table 1 Cell viability treated with different concentrations of fish skin protein
[0052] Concentration (μg / mL) Cell survival rate (%) 0 <![CDATA[100±0.30 b ]]> 5 <![CDATA[99.6±2.77 b ]]> 25 <![CDATA[102.24±6.79 b ]]> 50 <![CDATA[104.03±0.84 b ]]> 100 <![CDATA[104.93±1.26 b ]]> 200 <![CDATA[115.75±5.41 a ]]>
[0053] Example 2 Antioxidant activity of fish skin protein
[0054] ABTS + Method: Mix 7.4mM ABTS solution (ABTS, Shanghai MacLean Biochemical Technology Co., Ltd., Catalog No. 30931-67-0) and 2.6mM potassium persulfate solution (potassium persulfate, Tianjin Fengchuan Chemical Reagent Technology Co., Ltd., Catalog No. 7727-21-1) in equal volumes and allow them to react fully to obtain green ABTS. + The free radical solution was then diluted 15 times with ultrapure water to finally make ABTS + The solution was stirred until its absorbance at 732 nm was about 0.6. The fish skin protein prepared in Example 1 was dissolved in water to prepare fish skin protein solutions with concentrations of 1wt%, 2wt%, 4wt% and 6wt%, respectively. 200 μL of samples of different concentrations were mixed with 600 μL of diluted ABTS. + The solutions were mixed and allowed to stand for 30 min in the dark, and the absorbance of the final mixed solution was measured at 732 nm using an ultraviolet spectrophotometer.
[0055]
[0056] Wherein, A0 is the absorbance (732nm) of the solution treated with ultrapure water, A i is the absorbance (732 nm) of the resulting solution treated with different samples (experimental groups).
[0057] like Figure 2 As shown in Table 2, ABTS treated with different concentrations of FSP +The absorbance of the solution at 732 nm gradually decreased with the increase of FSP, indicating that the extracted FSP has good ABTS + The free radical scavenging ability showed good antioxidant activity, and the difference between different concentrations was very significant.
[0058] Table 2 ABTS of fish skin protein at different concentrations + Clearance
[0059] Concentration (mg / mL) <![CDATA[ABTS + Clearance rate (%)]]> 1 <![CDATA[22.33±0.98 d ]]> 2 <![CDATA[44.52±0.7 c ]]> 4 <![CDATA[56.46±0.56 b ]]> 6 <![CDATA[65.79±0.06 a ]]>
[0060] Example 3 Preparation of RA@FSP / CS NCs nanodelivery system
[0061] First, 0.1g of chitosan was dissolved in 100mL of 1% (v / v) acetic acid aqueous solution to obtain a chitosan solution with a solubility of 0.1wt%, and magnetic stirring was used to prevent chitosan from hanging on the wall. The fish skin protein extracted in Example 1 was dissolved in pure water and dissolved in a 37°C water bath to obtain a fish skin protein aqueous solution with a solubility of 0.1wt%, and magnetic stirring was used to fully dissolve the fish skin protein. The fish skin protein aqueous solution was added to the chitosan solution under magnetic stirring to obtain a wall material solution. In the wall material solution, the mass ratios of FSP and CS were 5:0, 4:1, 3:2, 2:3, 1:4, and 0:5, respectively. The wall material solution (i.e., blank nanocomposite material) was named FSP / CS according to the mass ratios of FSP and CS. 50 NCs, FSP / CS 41 NCs, FSP / CS 32 NCs, FSP / CS 23 NCs, FSP / CS 14 NCs and FSP / CS 05 NCs.
[0062] Dissolve rosmarinic acid in water to obtain a concentration of 100 μg mL -1 1 mL of 100 μg mL rosmarinic acid aqueous solution was stirred under magnetic stirring. -1 The rosmarinic acid aqueous solution was added dropwise into 10 mL of wall material solutions with different mass ratios, and the pH of the above system was adjusted to about pH = 7 with 1 M NaOH solution and 1 M acetic acid solution. The stirring was continued for 10 min to form a uniform system to obtain a liquid nano delivery system material. The liquid nano delivery system material was freeze-dried for 48 h to obtain a solid material of the nano delivery system.
[0063] The obtained nano-delivery system materials were named RA@FSP / CS according to the mass ratio of FSP and CS. 50 NCs, RA@FSP / CS 41 NCs, RA@FSP / CS32 NCs, RA@FSP / CS 23 NCs, RA@FSP / CS 14 NCs and RA@FSP / CS 05 NCs.
[0064] The prepared liquid nano-delivery system material is shown in the figure below: Figure 3 As shown in the figure, the higher the proportion of CS, the higher the micelle height, indicating that more FSP / CS nanocomposites are formed. The prepared liquid nano-delivery system material was observed microscopically, as shown in the figure. Figure 4 As shown in a and b, when the ratio of FSP / CS is 2:3, the blank nanocomposite material (FSP / CS 23 NCs) and RA-loaded nano-delivery system materials (RA@FSP / CS 23 The micelle height of RA@FSP / CS 23 NCs showed a higher 23 NCs have a denser microstructure. Figure 4 Figures c and d show that the addition of RA helps to form a denser nanostructure in the nanodelivery system. This denser nanostructure may be due to the presence of four phenolic hydroxyl groups and one carboxyl group in the RA molecule, which can interact with the NH groups in the protein molecules to form hydrogen bonds, thereby acting as a "bridge" between molecules. This interaction increases the cohesion within the nanodelivery system material and enhances the dominant role of non-covalent interactions between FSP, CS, and RA. Figure 4 In e and f, TEM results show that RA@FSP / CS 23 NCs have a more obvious spherical structure, which is different from FSP / CS 23 NCs are more regular than those of RA@FSP / CS, indicating that the introduction of RA significantly improves the 23 NCs microstructure.
[0065] Example 4 Encapsulation efficiency of RA in RA@FSP / CS NCs nano-delivery system material
[0066] RA encapsulation efficiency under different conditions: RA@FSP / CS NCs were determined by UV spectrophotometry. First, a certain concentration gradient (1 μg mL -1 , 5μg·mL -1 , 10μg·mL -1 , 20μg·mL -1 , 30μg·mL -1 , 40 μg·mL-1 , 50μg·mL -1 ) standard RA solution, then collect its UV spectrum in the range of 200-800nm, and use a UV spectrophotometer to record its peak absorbance at 325nm.
[0067] Next, the RA@FSP / CS NCs liquid nano-delivery system material prepared in Example 3 was centrifuged to determine the content of RA in the supernatant, and then the encapsulation efficiency of RA was calculated according to the following formula:
[0068]
[0069] Where m0 is the mass of RA initially added and m1 is the content of RA in the supernatant.
[0070] like Figure 5 As shown in Table 3, the encapsulation efficiency of RA increased from 57.43% to 81.47% with the increase of CS ratio. When the ratio of fish skin protein to chitosan changed from 3:2 to 2:3, the encapsulation efficiency of RA increased from 60.68% to 71.42%, indicating that chitosan significantly improved the encapsulation efficiency of RA. This improvement may also be attributed to the interaction between RA, CS and FSP, which promoted the embedding of RA in FSP / CS wall material.
[0071] Table 3 Encapsulation efficiency of RA in RA@FSP / CS NCs at different FSP:CS wall material mass ratios
[0072] Nanocomposite Encapsulation rate (%) <![CDATA[RA@FSP / CS 50 NCs]]> <![CDATA[57.43±0.17 e ]]> <![CDATA[RA@FSP / CS 41 NCs]]> <![CDATA[59.28±0.18 d ]]> <![CDATA[RA@FSP / CS 32 NCs]]> <![CDATA[60.69±0.19 c ]]> <![CDATA[RA@FSP / CS 23 NCs]]> <![CDATA[71.43±0.19 b ]]> <![CDATA[RA@FSP / CS 14 NCs]]> <![CDATA[71.76±0.12 b ]]> <![CDATA[RA@FSP / CS 05 NCs]]> <![CDATA[81.47±0.21 a ]]>
[0073] Example 5 ABTS of RA@FSP / CS NCs Nano-delivery System Materials + clearance rate.
[0074] Mix 7.4 mM ABTS solution and 2.6 mM potassium persulfate solution in equal volumes to react completely to obtain ABTS + The free radical stock solution was diluted with ultrapure water until the absorbance at 732 nm was 0.6. Next, 200 μL of RA@FSP / CS prepared in Example 3 was added. 50 NCs, RA@FSP / CS 41 NCs, RA@FSP / CS 32 NCs, RA@FSP / CS 23 NCs, RA@FSP / CS 14 NCs and RA@FSP / CS 05 NCs liquid nano-delivery system materials were mixed with 600 μL diluted ABTS +The solutions were mixed and placed in the dark for 30 min. The absorbance of the final mixture was measured at 732 nm by UV spectrophotometer. The absorbance of ultrapure water treatment was used as a control. Finally, the antioxidant activity was recorded as ABTS + Free Radical Scavenging Activity:
[0075]
[0076] Where A0 is the absorbance (732 nm) of the solution treated with ultrapure water, A i is the absorbance (732 nm) of the resulting solution treated with different samples (experimental groups).
[0077] Figure 6 a in the figure is the ABTS of RA@FSP / CS NCs + The clearing activity is intuitively shown in Figure 1. The lighter the color, the more ABTS + The higher the clearance rate, the higher the RA@FSP / CS 23 NCs has the lightest color. Figure 6 As shown in b, c and Table 4, when the FSP / CS ratio is 2:3, RA@FSP / CS 23 NCs showed the best antioxidant activity among all groups, ABTS + The free radical scavenging rate was 61.86%. The second was RA@FSP / CS 50 NCs, ABTS + The free radical scavenging rate was 58.88%. RA@FSP / CS 32 ABTS of NCs + The free radical scavenging rate was the lowest, at 18.67%.
[0078] Table 4 ABTS of RA@FSP / CS NCs at different FSP:CS wall material mass ratios + Clearance
[0079]
[0080]
[0081] Example 6 RA@FSP / CS 23 ABTS of NCs Nano-delivery System Materials + The clearance rate
[0082] Adopting ABTS + The antioxidant activity of RA@FSP / CS NCs was determined by the method. 800 μL ABTS was added into a 1.5 mL centrifuge tube. + Free radical solution, added with different volumes of RA@FSP / CS prepared in Example 3 23NCs liquid nanodelivery system materials (20 μL, 40 μL, 60 μL, 80 μL, 100 μL, 1 mg / mL) and different volumes of ultrapure water (80 μL, 60 μL, 40 μL, 20 μL, 0 μL) were added to ensure that the obtained solutions had the same volume. The absorbance of 100 μL ultrapure water was used as a control. Then, the obtained solution was stored in the dark for 30 min, and then its absorbance at 732 nm was measured using a UV spectrophotometer. Finally, the antioxidant activity was recorded as ABTS + Free Radical Scavenging Activity:
[0083]
[0084] Where A0 is the absorbance (732 nm) of the solution treated with ultrapure water, A i is the absorbance (732 nm) of the resulting solution treated with different samples (experimental groups).
[0085] like Figure 7 As shown in Table 5: With the increase of RA@FSP / CS 23 As the amount of NCs added increases, ABTS + These findings suggest that RA@FSP / CS 23 NCs have significant antioxidant activity, which is positively correlated with their concentration. 23 The high antioxidant capacity of NCs is mainly attributed to the o-diphenolic hydroxyl group and the conjugated double bond at the C-3 position in the RA structure.
[0086] Table 5 RA@FSP / CS 23 ABTS of NCs + Clearance
[0087] Addition amount (μL, 1mg / mL) <![CDATA[ABTS + Clearance rate (%)]]> 20 <![CDATA[3.15±0.02 e ]]> 40 <![CDATA[5.97±0.04 d ]]> 60 <![CDATA[17.09±0.04 c ]]> 80 <![CDATA[25.91±0.02 b ]]> 100 <![CDATA[45.21±0.02 a ]]>
[0088] Example 7 RA@FSP / CS 23 Scavenging rate of hydroxyl radicals (·OH) in NCs nanodelivery system materials
[0089] First, 600 μL of 0.75% (w / v) H2O2 and 200 μL of 2.5 mM FeSO4 (ferrous sulfate, Sigma-Aldrich Biotechnology Co., Ltd. (Beijing), catalog number 7782-63-0) were mixed to generate ·OH through Fenton reaction (10 min). Then, 0 μL, 10 μL, 20 μL, 40 μL, 60 μL, 80 μL, and 100 μL of RA@FSP / CS prepared in Example 3 were added to the mixed solution. 23NCs liquid nano-delivery system material (1 mg / mL) eliminates ·OH, TMB (3,3',5,5'-tetramethylbenzidine) (TMB, Shanghai Aladdin Biochemical Technology Co., Ltd., catalog number 54827-17-7) is dissolved in ethanol and prepared to a concentration of 10mM, and finally 200μL 10mM TMB is added to detect the remaining ·OH. Ultrapure water treatment is used as a control. The ·OH clearance rate is calculated as shown in the formula:
[0090]
[0091] A0 is the control group, A i For the sample group.
[0092] Figure 8 a stands for RA@FSP / CS 23 The intuitive diagram of ·OH scavenging activity of NCs. The lighter the color, the higher the ·OH scavenging rate. 23 The color becomes lighter as the concentration of NCs increases. 23 The higher the concentration of NCs, the higher the scavenging rate of hydroxyl radicals (·OH). Figure 8 As shown in b, c and Table 6, with the increase of RA@FSP / CS 23 The larger the amount of NCs added, the higher the scavenging rate of hydroxyl radicals (·OH).
[0093] Table 6 RA@FSP / CS 23 Hydroxyl radical (·OH) scavenging rate of NCs
[0094] Unit (μL, 1mg / mL) OH removal rate (%) 10 <![CDATA[69.23±0.45 f ]]> 20 <![CDATA[85.79±0.15 e ]]> 40 <![CDATA[91.05±0.03 d ]]> 60 <![CDATA[94.48±0.06 c ]]> 80 <![CDATA[95.70±0.12 b ]]> 100 <![CDATA[97.13±0.04 a ]]>
[0095] Example 8 RA@FSP / CS 23 Thermal stability analysis of NCs nano-delivery system materials
[0096] The sample detection amount was 10 mg, and the sample was heated from room temperature to 730°C at a heating rate of 10°C / min. The RA and FSP / CS prepared in Example 3 were analyzed by thermogravimetric analyzer. 23 NCs and RA@FSP / CS 23 Thermogravimetric analysis of NCs solid-state nanodelivery system materials.
[0097] like Fig. 9 As shown, the initial degradation temperatures of the first and second stages of RA are significantly lower than those of FSP / CS. 23 NCs and RA@FSP / CS 23 NCs nanoparticles, FSP / CS 23 The starting temperature of the second stage of degradation of NCs nanoparticles is 104℃, and the RA@FSP / CS23 The initial degradation temperature of the second stage of NCs is 124℃, and after the degradation is completed, RA@FSP / CS 23 The residual substances in NCs were higher than those in RA and FSP / CS. 23 There are many NCs, indicating that RA@FSP / CS 23 NCs compared with RA and FSP / CS 23 The thermal stability of NCs was improved.
[0098] It can be seen that the nano-delivery system (RA@FSP / CS NCs) of the present invention not only maintains the excellent antioxidant activity of RA, but also has good stability. + Free radicals and hydroxyl (·OH) radicals are expected to be applied to the stabilization of food functional factors or nutrients and the maintenance of antioxidant activity.
[0099] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A rosmarinic acid nano delivery system, characterized in that: The rosmarinic acid nano delivery system comprises a wall material and inclusions; the wall material comprises fish skin protein and / or chitosan; and the inclusions comprise rosmarinic acid.
2. The rosmarinic acid nano delivery system according to claim 1, characterized in that: The mass ratio of the fish skin protein to chitosan is 0-5:0-5.
3. The rosmarinic acid nano delivery system according to claim 2, characterized in that: The fish skin protein includes black fish skin protein.
4. The method for preparing the rosmarinic acid nano delivery system according to any one of claims 1 to 3, characterized in that: The following steps are involved: The rosmarinic acid aqueous solution is added dropwise into the wall material solution, and freeze-dried to obtain the rosmarinic acid nano delivery system.
5. The preparation method according to claim 4, characterized in that: The wall material solution includes a fish skin protein aqueous solution and / or a chitosan solution; the mass ratio of the fish skin protein to the chitosan is 0-5:0-5.
6. The preparation method according to claim 5, characterized in that: The concentration of the chitosan solution is 0.1 wt %; the concentration of the fish skin protein aqueous solution is 0.1 wt %; the concentration of the rosmarinic acid aqueous solution is 100 μg·mL -1 .
7. The preparation method according to claim 8, characterized in that: The volume ratio of the rosmarinic acid aqueous solution to the wall material solution is 0.5-1.5:8-12.
8. The preparation method according to claim 7, characterized in that: The freeze-drying time is 36 to 48 hours.
9. The preparation method according to claim 8, characterized in that: After the rosmarinic acid aqueous solution is added dropwise into the wall material solution, the method further comprises adjusting the pH value of the rosmarinic acid nano delivery system to 6.8-7.
2.
10. Use of the rosmarinic acid nano delivery system according to any one of claims 1 to 3 or the rosmarinic acid nano delivery system prepared by the preparation method according to any one of claims 4 to 9 in the preparation of functional foods.